Evaluasi Penyimpanan dan Distribusi Obat dengan Pendekatan Siklus Manajemen Logistik di Instalasi Farmasi RS. Hermina Jatinegara Tahun 2022 - Naomi Aulia S Adjie; Ascobat Gani (Syntax Literate, 2022)
The process of storing and distributing drugs is part of the logistics management cycle. Improper storage of the drug can result in damage or loss of the drug in the hospital therefore the drug must be properly stored so that it is stored and then distributed to the patient. For the distribution of drugs, the safety and accuracy of drugs provided by pharmacy facilities, the accuracy of the patient, the accuracy of the schedule, the date, time, mode of administration, the personal accuracy of the drug giver to the patient and medicine. This study aims to examine the storage and distribution of drugs using a logistics management cycle approach at the pharmaceutical facility of Hermina Jatinegara hospital. The research methodology is descriptive and qualitative through in-depth interviews with informants with interview guides. As a result, it was found that the Pharmaceutical Installation of Hermina Jatinegara Hospital in implementing the procedures for storing and distributing drugs in warehouses was mostly in accordance with the provisions in the hospital pharmaceutical service standards based on the Regulation of the Minister of Health No. 72 of 2016. Drug distribution uses a decentralized method, so that all medicines and medical devices are served separately from the Pharmaceutical Installation.